2020
DOI: 10.1101/2020.06.26.20140798
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Idiopathic and acquired pedophilia as two distinct disorders: an insight from neuroimaging

Abstract: Objective: Pedophilia is a disorder of public concern because of its association with child sexual offense and recidivism. Previous neuroimaging studies identified inconsistent brain abnormalities underlying pedophilic behavior both in idiopathic and acquired (i.e., emerging following brain damage) pedophilia. This study sought to explore the neural underpinnings of pedophilic behavior and to determine the extent to which brain alterations may be related to distinct psychopathological features in pedophilia. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In view of the present results, the same conclusion can be drawn about acquired pedophilia. Interestingly, a recent brain imaging meta-analysis based on 436 men with a pedophilic disorder failed to find any structural difference compared with 449 controls (Scarpazza et al, 2021). Therefore, anomalies of fronto-temporal regions appear to be more closely associated with child sexual abuse (acting out) than pedophilia (Dillien et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In view of the present results, the same conclusion can be drawn about acquired pedophilia. Interestingly, a recent brain imaging meta-analysis based on 436 men with a pedophilic disorder failed to find any structural difference compared with 449 controls (Scarpazza et al, 2021). Therefore, anomalies of fronto-temporal regions appear to be more closely associated with child sexual abuse (acting out) than pedophilia (Dillien et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…How ever, Baird also stated (correctly) that "those who do develop paedophilia in the context of a neurological condition typically show general behavioural 'disinhibition'" (p. 113). Indeed, a growing number of authors consider acquired pedophilia as a symptom of a larger disinhibition syndrome (Kruger & Kneer, 2021;Scarpazza et al, 2021). For instance, after reviewing 19 cases of acquired pedophilia, Scarpazza and colleagues (2021) reported that they all suffered from a more general impulse control syndrome.…”
Section: Brain Damage Deviant Sexual Behaviors and Impulsivitymentioning
confidence: 99%
See 1 more Smart Citation
“…While certain ethical aspects also are involved (118), the neuro-scientific approach offers a strategy to mitigate these problems, as it adopts methods with significantly lower error rates than the classical assessment. Thus results from unstructured clinical interviews should be integrated with data from standardized and objective neuropsychological and psychopathological tests (31,33) and from laboratory exams (9,22,119) and interpreted in respect of the convergence of evidence principle (14,120).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the major limitation to the introduction of a neuroscientific approach into the legal settings does not come from the judges and jurors, but from scientists themselves who, in accordance with the denial cognitive bias (40,48), prefer to maintain a disputable methodology rather than to improve the overall procedure by adopting a multidisciplinary approach based on the convergence of evidence principle. This problem appears to be specific for forensic psychiatry, while it is not present in clinical psychiatry, as demonstrated by the constant growing of studies that search for potential ways to enhance translational application of neuro-scientific findings into clinical psychiatric settings (53,110,119,(121)(122)(123)(124).…”
Section: Discussionmentioning
confidence: 99%